EFFECT OF GOALBALL SPORT ON PHYSICAL PERFORMANCE OF VISUALLY IMPAIRED STUDENTS (JOURNAL OF SOCIAL SCIENCE RESEARCH, 2015)
The aim of this study was to examine the effect of three month goalball sport on physical performance of visually impaired students. 38 visually impaired male students attending to the primary school were participated the study. 19 of them were separated as an exercise group (age; 13.15Â±1.59 years) and the rest 19 subject were separated as a control group (age; 13.30Â±1.43years) randomly. Exercise group do goalball sport three days a week for three months. Before and after the exercise program some physical performance tests were applied to all 38 students. To measure the physical performance; audial reaction time, 10 m running time, standing long jump, grip strength, vertical jump, and flexibility values were measured. The physical performance measured before the start of the three month exercise did not show meaningful difference between two groups (p>0.05). But when the values after three month were compared, it was found that audial reaction time, standing long jump, grip strength, 10 m speed running time, vertical jump and flexibility levels of the group doing goalball exercise was statistically better than that of the control group (p